The Impact Of Environmental Management Practices On Manufacturing Firms Performance In Java, Indonesia - Hasyim, Ina Indriyana (2022)
Business activities contribution to national income is significant. However, its rapid development, that is not harmonized with environmentally friendly practices, has a negative impact on the environment. Minimizing the negative impact on the environment, stakeholders call firms not only focus on achieving short-term financial performance but also focus on handling the adverse environmental effects of firm activities. An environmental management practices is implemented to mitigate environmental problems. The study is directed to estimate the effect of manufacturing industry on environmental quality, examine the role of firm environmental performance in mediating the relationship between environmental management systems, green innovation, and firm profitability, and investigate the role of green innovation, training as mediator variable in the relationship between environmental management system and firm environmental performance.